Secret state of North Korea (PBS Distribution, 2014)
"Just two years into the job and armed with nuclear weapons, North Korea's Kim Jong-un is the world's youngest dictator, ruling one of the world's most isolated countries ... Using new footage smuggled from inside and never-before-told stories from recent defectors living in South Korea, the film offers a rare glimpse at how some North Koreans are defying authority in a country where just being caught with illegal DVDs could mean immediate imprisonment"--Container.